The influence of functional states on the normative indicators of cross-country running of students before and after the COVID-19 pandemic - Zaitseva, I. P. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to assess the impact of functional states on the performance of normative indicators of cross-country running of students before and after the COVID-19 pandemic.